Social Media and Political Mobilisation: An Analysis of the July 2016 Zimbabwe Shut Down - Mutanana, Ngonidzashe (American Journal of Trade and Policy, 2017)
This study sought to carry out an analysis of the effects of the social media in political mobilization. These were analyzed using the following indicators (i) the social media as a communication tool and (ii) the role of social media in political mobilization. The study was using a one-day demonstration that occurred in Zimbabwe code named #ZimShutDown2016 as a case study. In the study, a qualitative case study research design was used. Secondary data from online newspaper reports and Social Media Networks was used to analyze the effects of the social media movement in bringing real socio-economic and political change in developing countries such as Zimbabwe. In-depth interviews with five key informants from local universities helped in the analysis and they were identified using purposive sampling technique. Findings from the study revealed that social media is an effective tool of communication among citizens. Information is exchanged minute by minute among citizens, and this encourages ‘citizenry journalism.’ As such, the social media has a positive impact in mobilizing the community in bringing real social, political and economic change. The study, therefore, recommends a longer survey on the challenges of the social media movement in developing countries such as Zimbabwe.